Distribution and diversity of earthworms in different land use systems in Rio Grande do Sul, Brazil - Ferreira, Talita; James, Samuel W.; Bartz, Marie Luise Carolina; de Lima, Ana Claudia Rodrigues; Dudas, Rafaela; Brown, George Gardner (Zootaxa, 2023)
The southernmost state of Brazil, Rio Grande do Sul, includes both the Pampa and Atlantic Forest biomes, and covers an area of around 284 thousand km2. Since the last checklist for the state, published in 2012, many additional sites have been sampled. Hence, we provide here a full list of earthworm species and their distribution in different municipalities and land use systems in the state. Data were obtained from the literature, museums, and other earthworm collections and recent sampling efforts. Records for 19 additional species are reported here for the first time, raising the total to 78 species/subspecies currently known from Rio Grande do Sul, from the families Acanthodrilidae (5), Benhamiidae (3), Lumbricidae (13), Megascolecidae (11), Ocnerodrilidae (22), Almidae (2), Glossoscolecidae (18) and Rhinodrilidae (5). Alexidrilus Righi, 1971 is synonymized with Urobenus Benham, 1886, as both species in the genus (A. littoralis Ljungström, 1972 and A. lourdesae Righi, 1971) have similar morphology to the type species Urobenus brasiliensis Benham, 1886. Most of the native species/subspecies in the state (39), including an important number of new species, were found in native vegetation with lesser disturbance, such as swamps, native forests and pastures. On the other hand, the three peregrine and 27 exotic species (especially Pontoscolex corethrurus, Eukerria spp., lumbricids, megascolecids, Dichogaster spp., and Microscolex spp.) dominated in disturbed sites, such as compost piles, urban areas, rice and other crops, and cultivated pastures. Considering the geographic extension and the many unsampled sites in the state, further collection efforts are necessary and will certainly reveal new species, as evidenced here.